Pengaruh Atribut Produk, Kualitas Produk Dan Promosi, Terhadap Keputusan Pembelian Mobil Merek Honda Di Kota Medan - Bunga Aditi; HM Hermansyur (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study aims to identify and explain the influence of product attributes, product quality, and partial and simultaneous promotion on purchasing decisions. This type of research is explanatory research with a quantitative approach. Sampling using Non-Probability Sampling is the saturated sampling of 100 respondents using multiple linear regression analysis techniques. The results showed that the variable product attributes, product quality, promotion of partially significant effect on purchasing decisions. The results of the simultaneous shows that the variable product attributes, product quality, and promotion significantly influence purchasing decisions. Therefore, the company should be able to inform the Honda brand car with a better understanding of product attributes, product quality, and price through the sales conversations, so that they are understood in marketing their products.